n 3 + ( n + 1 ) 3 + ( n + 2 ) 3 = ( n + 3 ) 3
How many real solution(s) are there to the above equation?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
From which we get 3 3 + 4 3 + 5 3 = 6 3 . Nice solution. +1
How do you get from 2 ( n 3 − 6 n − 9 ) = 0 to 2 ( n − 3 ) ( n 2 + 3 n + 3 ) = 0 ?
Problem Loading...
Note Loading...
Set Loading...
n 3 + ( n + 1 ) 3 + ( n + 2 ) 3 = ( n + 3 ) 3
n 3 + ( n 3 + 3 n 2 + 3 n + 1 ) + ( n 3 + 6 n 2 + 1 2 n + 8 ) = ( n 3 + 9 n 2 + 2 7 n + 2 7 )
⟹ 3 n 3 + 9 n 2 + 1 5 n + 9 = n 3 + 9 n 2 + 2 7 n + 2 7
⟹ 2 n 3 − 1 2 n − 1 8 = 0 ⟹ 2 ( n − 3 ) ( n 2 + 3 n + 3 ) = 0
The solutions for n are 3 , 2 3 + 3 i , 2 3 − 3 i . Thus, there is only 1 real solution.